ESD-Based Outdoor Learning in Animal Biosystematics Course: A Strategy to Improve Students' Understanding of Conservation - Saefudin; Anugrah Ayumaharani Widianingsih; Fitri Husni Mardiyah; Suhara (Universitas Veteran Bangun Nusantara Sukoharjo, 2026)
This study aims to explore the extent to which outdoor learning grounded in Education for Sustainable Development (ESD) enhances students' conceptual grasp of biodiversity, evolution, and conservation. Thirty-seven undergraduate biology education students participated in this study, which employed a quasi-experimental one-group pretest-posttest design in the Animal Biosystematics course. Data were collected using a standardized questionnaire and written cognition tests. The results showed a statistically significant improvement in students' posttest scores (M = 90.24, SD = 4.98) compared to their pretest scores (M = 81.29, SD = 3.65), with a significant effect t (36) = - 25.049, p < .001, Cohen's d = 2.17). The study of questionnaire responses revealed that over 88% of students had positive perceptions about the utilization of outdoor learning in four key areas: participation (who), learning content (what), learning environment (where), and instructional approach (how). Additionally, more than 67% of students stated they would be open to participating in future outdoor learning activities and planning that are based on ESD. Additionally, students stated that the educational experience raised their critical understanding of conservation and sustainability issues. These results imply that ESD-focused outdoor learning is an effective teaching method to promote ecological awareness and active student participation in biology classes with a sustainability focus.